From public health to international law: possible protocols for inclusion in the Framework Convention on Tobacco Control - Luk Joossens (The World Health Organization, 2000)
Faced with a difficult business environment in the United States and the falling demand for cigarettes in industrialized countries, multinational tobacco companies have been competing fiercely to expand their sales in developing countries. Because of the worldwide threat posed by smoking to health and the emphasis being placed by international tobacco companies on marketing in developing countries, an international regulatory strategy, such as the WHO proposed Framework Convention on Tobacco Control, is needed. This review describes from a public health perspective the possible scope and key considerations of protocols that should be included in the convention. The key international areas that should be considered in tobacco control are: prices, smuggling; tax-free tobacco products; advertising and sponsorship; the Internet; testing methods; package design and labelling; agriculture; and information sharing.